Maize responds to low shoot P concentration by altering root morphology rather than increasing root exudation - Wen, Zhihui; Li, Haigang; Shen, Jianbo; Rengel, Zed (Plant and soil, 2017)
Background and aims Alterations in root growth and rhizosphere processes in maize (Zea mays L.) occur under phosphorus (P) deficiency, but the dynamics of root morphological and physiological modifications with increasing shoot P concentration remain unclear. This study investigated root responses to a wide gradient in shoot P status. Methods A range of maize shoot P concentrations (1.0–4.0 mg g−1) was established using controlled pot experiment with eleven rates of P supply from 0 to 1200 mg P kg−1 soil. Root morphology and rhizosphere processes were characterized 28 days after planting. Results Maize reached maximum biomass at shoot P concentration of 2.7 mg g−1. Root morphological responses (i.e. total root length, specific root length and proportion of fine roots) showed a strong increasing trend with decreasing shoot P concentration (1.1–1.3 mg g−1), but they decreased when shoot P concentration was extremely low (below 1.1 mg g−1). In contrast, with increasing shoot P concentration, root morphological responses decreased, but root physiological responses (rhizosphere acidification, acid phosphatase activity and carboxylate exudation in the rhizosphere) were enhanced, and no decrease was noted even at high shoot P concentration (4.0 mg g−1) corresponding to excess P supply. Conclusions Increasing maize shoot P concentration induced a decrease in root morphological responses and an enhancement in root exudation, with maize response to P deficiency being dependent on root morphological rather than physiological traits.